2017
DOI: 10.1002/ece3.3285
|View full text |Cite
|
Sign up to set email alerts
|

Clonal structure through space and time: High stability in the holothurianStichopus chloronotus(Echinodermata)

Abstract: Sea cucumbers are increasingly exploited for human consumption and for their curative properties, and many wild populations are now depleted or in danger of extinction. While aquaculture is seen as an alternative to fisheries and as a mean to restore wild populations, more knowledge is needed on their reproductive strategies to render this practice efficient, notably for fissiparous holothurians, which are some of the mobile animals able of asexual reproduction by transverse fission. Little information is avai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(19 citation statements)
references
References 59 publications
(82 reference statements)
1
2
0
Order By: Relevance
“…The global FST between both seasons (0.019 NS ) suggests no genetic differentiation and thus, temporal stability in this H. atra population. The stability observed through time for H. atra was also found for S. chloronotus [14].…”
Section: Population Structuresupporting
confidence: 52%
See 2 more Smart Citations
“…The global FST between both seasons (0.019 NS ) suggests no genetic differentiation and thus, temporal stability in this H. atra population. The stability observed through time for H. atra was also found for S. chloronotus [14].…”
Section: Population Structuresupporting
confidence: 52%
“…The absence of identical MLGs in our dataset may be due to the high number of loci used decreasing mathematically the probability to find two identical MLGs over the 42 alleles, and also their inherent high polymorphism. Indeed, reducing the number of loci used, to be able to compare clonal richnesses among studies (1,000 sub-datasets from the random selection of nine microsatellites over the 21 specific for H. atra), the mean clonal richness in H. atra reached 0.91 ± 0.002 [± SE; min: 0.63 (28 MLGs); max: 1 (44 MLGs)] and remained extremely high comparatively to the one found in S. chloronotus populations (R = 0.09) [14]. Indeed, in S. chloronotus, each population (based on 64 sampled individuals per site × season) was comprised of one to three dominant MLGs [14], although the percentage of S. chloronotus individuals issued from asexual reproduction estimated based on body shape few decades ago was quite low (6.5%) [24].…”
Section: Clonal Propagationmentioning
confidence: 93%
See 1 more Smart Citation
“…Two additional sites with low densities (<0.1 ind•m −2 , personal observations) were studied: CAP (Cap Méchant) and PTE (Petit Trou d'Eau) (Figure 1). Individuals of S. chloronotus were sampled in the same high density sites as in a previous study [31]: PAS (Passe de l'Hermitage; corresponding to HIGH1 in [31]; with a density of 0.…”
Section: Spatial Samplingmentioning
confidence: 99%
“…The number of individuals of S. chloronotus performing fission has been estimated to 17% at Reunion Island [24], using the same method as for H. leucospilota [23]. However, two decades later, the clonal richness was analysed using nine microsatellite markers [31] and authors concluded that it was extremely low (R = 0.09), meaning that many individuals of S. chloronotus are clones, and therefore, have participated or participate to asexual reproduction. Visual census is not a good predictor to estimate clonal propagation, as concluded by a study on Holothuria atra [32].…”
Section: Introductionmentioning
confidence: 99%